Determinants of Vancomycin Trough Concentration in Patients Receiving Continuous Veno-Venous Hemodialysis. Issue 10 (October 2022) - Quinn, Nicholas J.; Sacha, Gretchen L.; Wanek, Matthew R.; Yerke, Jason; Srinivas, Pavithra; Hohlfelder, Benjamin
Background: Vancomycin pharmacokinetics are altered in the critically ill and are further distorted by renal replacement therapy. Limited literature is available evaluating vancomycin dosing in continuous veno-venous hemodialysis (CVVHD). Objective: The goal of this analysis was to identify factors that affect vancomycin trough concentration in patients on CVVHD and to determine an appropriate dosing strategy. Methods: This was a single-center, retrospective cohort study of adult inpatients admitted to the Cleveland Clinic from May 2016-December 2017. Patients in the intensive care unit who received ≥ 2 doses of vancomycin during CVVHD were included. Patients with interruptions of CVVHD inappropriately timed troughs, a change in dialysate rate, and those who received different vancomycin dosages were excluded. Multivariable linear regression including age, sex, weight, Sequential Organ Failure Assessment score, albumin, 24-hour urine output (UOP), dialysate rate, filter type, and vancomycin dose was run to determine predictors of vancomycin concentration. Results: A total of 160 patients were included. The median vancomycin dose was 12.6 mg/kg with a trough of 24.6 mcg/mL. Weight, 24-hour UOP, vancomycin dose (mg/kg), and dialysate rate (mL/kg/h) were all determined to be independent predictors of vancomycin trough level. Patients who received <10 mg/kg doses of vancomycin (N=18) achieved a median trough of 21.5 mcg/mL, with 83% being therapuetic. In patients who received >10 mg/kg (N=142), the median trough was 25.5 mcg/mL, with 47% being therapeutic. Conclusion and Relevance: Vancomycin dose, dialysate rate, UOP, and weight are independently associated with vancomycin trough concentration. In CVVHD patients, vancomycin dosed at 10 mg/kg every 24 hours may be an appropriate recommendation.